(untitled) (Indian Journal of Arid Horticulture, 2025)
The pollen morphology and germination percentage of guava cultivars during two flowering seasons viz., spring (April-May) and autumn (August-September) were observed. Pollen grain germination was recorded best in two hours after pollination in 12 per cent sucrose solution. Pollen size as well as pollen tube length was recorded larger in cultivar Lucknow-49 as compared to other cultivars.